Circadian rhythm disruption and polycystic ovary syndrome: a systematic review and meta-analysisAJOG Global Reports at a Glance - Tara Heydari, MS; Prakash V.A.K. Ramdass, MD, MPH (AJOG Global Reports, 2025)
Objective: The aim of our systematic review and meta-analysis was to determine if circadian rhythm disruption (CRD) is associated with polycystic ovary syndrome (PCOS). Our objective was to pool the overall mean differences in biomarkers of CRD (including melatonin levels, morning and evening cortisol levels, and sleep efficiency) between PCOS patients and controls. We hypothesized that CRD will be more prominent in patients with PCOS. Data sources: A systematic search of PubMed, Scopus, Embase, ClinicalTrials.Gov, and the Cochrane Database of Systematic Reviews was conducted from inception until 2024 using the following MeSH terms “circadian rhythm” OR “sleep disturbance” OR “melatonin” AND “polycystic ovary syndrome.” Citation search supplemented the systematic database search. Study eligibility criteria: Inclusion criteria were women with PCOS, original case-control, cross-sectional, and cohort studies that identify parameters of CRD (melatonin, cortisol, and sleep disturbance). Exclusion criteria were women with endocrine and metabolic co-morbidities, menopausal women, case reports, review studies, animal studies, abstracts, and conference presentations. There was no time restriction for year of publication. Study appraisal and synthesis methods: Two investigators (T.H. and P.R.) assessed the quality of the studies included using the Newcastle-Ottawa Scale. Forest plots were created using the Open Meta Analyst software. Publication bias was assessed in Egger's and Begg's tests. Results: A total of 16 studies were included in the systematic review and 12 studies were included in the meta-analysis (N=1,100 women [531 PCOS patients and 569 controls]). Pooled analysis showed that the mean difference in melatonin levels between PCOS patients and controls was 14.294 pg/mL, 95% CI [6.895, 21.693]. The overall mean difference in morning and evening cortisol between PCOS patients and controls was 1.103 pg/mL, 95% CI [−1.058, 3.265], and 3.574 pg/mL, 95% CI [1.741, 5.407], respectively. Pooled difference in mean sleep efficiency scores between PCOS patients and controls was –4.059, 95% CI [−6.752, −1.366]. Risk of bias assessment showed that NOS scores ranged from 7 to 9. Conclusions: Our meta-analysis provides evidence that circadian rhythm disruption is positively associated with polycystic ovary syndrome. This is substantiated by differences in parameters indicative of circadian rhythm disruption, including melatonin levels, evening cortisol, and sleep efficiency.